Synonymy and notes on a rare species of Vriesea (Bromeliaceae) from the Atlantic forest hotspot of Bahia and Minas Gerais, Brazil - Versieux, Leonardo M.; Nogueira, Matheus; Conceição, Abel A. (Phytotaxa, 2018)
During the preparation of the Flora of Bahia we studied the sympatry of Vriesea noblickii Martinelli & Leme (1987: 346) and V. sandrae Leme (1995: 147) along the same mountain range in Santa Teresinha municipality. Fieldwork was conducted in similar vegetation along Bahia and Minas Gerais states and herbaria collections were revised aiming to comprehend their morphological variation. Here, we present an updated distribution and conservational comments about V. noblickii, including V. sandrae as a synonym. Although proposed earlier (Luther 2001), this synonymy has been ignored by most databases and the name V. sandrae is currently used for identifications of specimens from Bahia causing confusion. We also indicate a new record for northeastern Minas Gerais expanding the area occupied by V. noblickii.